Controlled fabrication of bismuth vanadium oxide hierarchical microtubes with enhanced visible light photocatalytic activity. (April 2015) - Ying, Yeqi; Tao, Feifei; Hong, Tianjie; Wang, Linxia
Abstract: Monoclinic bismuth vanadium oxide (BiVO4 ) hierarchical microtubes self-assembled by several nanowires have been successfully fabricated by a template-free approach. The morphology and structure of the as-prepared sample were characterized by scanning electron microscopy (SEM), X-ray powder diffraction (XRD) and UV–vis spectroscopy. BiVO4 microtubes have monoclinic structure with energy band gap of 2.36 eV. Based on the time-dependent experiments, the possible formation mechanism of BiVO4 microtubes was proposed. In addition, the photocatalytic activity of the as-prepared BiVO4 samples was evaluated by the degradation of methyl orange (MO) and various reactive dyes (RDs) under xenon lamp irradiation. In comparison with BiVO4 microrods, BiVO4 microtubes with hollow and porous structures showed higher photocatalytic activities and universality under visible-light irradiation. Due to the unique hierarchical hollow structures contributing to the increase of photocatalytic activities, BiVO4 microtubes exhibited the potential application as the promising visible-light photocatalyst.